Mechanistic insights into efficient reversible hydrogen storage in ferrotitanium. (1st January 2021) - Padhee, Satya Prakash; Roy, Amritendu; Pati, Soobhankar
Abstract: Although FeTi is a well-known hydrogen storage material, producing FeTi on a commercial scale is quite challenging, and generally, one ends up with a multi-phase system consisting of Fe2 Ti and FeTi. As Fe2 Ti is inert towards hydrogen, it lowers the hydrogen storage efficacy of FeTi. However, there are some reports, which propose that the presence Fe2 Ti in FeTi, primarily on the surface is inevitable and it helps in activation of FeTi. Here, we report results of targeted experiments together with first-principles density functional theory (DFT) based calculations to investigate the hydrogen storage properties of FeTi vis-à-vis origin of inertness of Fe2 Ti towards hydrogen storage. The formation enthalpies, calculated using density functional theory, of FeTi–H system were found to be very close to the experimental values (−28.1 and −33.72 kJ/mol H2 for FeTiH and FeTiH2 respectively), and that of Fe2 Ti–H systems was positive, indicating the inability to form stable intermetallic-hydrides. This corroborates well with the experimental observations, that the pure phase of Fe2 Ti cannot store hydrogen. Further, the Gibbs free energy for FeTiH and FeTiH2 were evaluated at 298 K using first-principles quantum mechanics and statistical thermodynamics theories. The vibrational and electronic entropies were calculated using Debye theory of heat capacities. Gibbs free energy at 298 K for FeTiH and FeTiH2 were found to be −5.01 and −3.52 kJ/mol of H2, respectively. Our present study concludes that proper care must be taken to avoid or minimize the formation of Fe2 Ti during the production of FeTi. Graphical abstract: Image 1 Highlights: FeTi and Fe2 Ti powders were ball milled and casted on Ni-foam. Cyclic voltammetry of ball milled samples were done for hydrogen storage testing. Fe2 Ti was inert towards hydrogen, as per cyclic voltammetry and DFT results. Formation energy of FeTiH and FeTiH2 were found to be −28.4 and −32.4 kJ/mol H2 . Gibb's energy at 298 K for FeTiH and FeTiH2 were found to be −5 and −3.5 kJ/mol H2 .